Geographical indications (GI) of spices, plantation, medicinal and aromatic crops - J, Sachin A; S, Karthik Nayaka V; Kalal, Prashant; S, Vijay Rakesh Reddy (Indian Horticulture, 2023)
Plantation and spice crops are the major commercial crops which are particularly grown under specific agro-climatic conditions. The unavailability of these commercial crops thoughout the country had led to increased adulterations and quality deteriorations which had resulted in reduced consumer acceptability of the products. The specific climatic conditions are majorly responsible for the unique quality of spices and plantation crops. With regards to these, geographical indications (GI) are helping the products in maintaining the quality specifications and also conserving the uniqueness of the product. Among the GI tagged horticultural crop’s plantation, spices, medicinal and aromatic crops cover around 36% share. This includes major crops like coffee, tea, coconut, chilli, turmeric, ginger, cardamom, Tejpat (Indian bay leaf), jasmine, betel vine and kewda. Registration of crops under GI has seen a substantial progress over the years in plantation and spice sector but with respect to medicinal and aromatic crops the GI tags are very few which requires an immediate attention/awareness among the farmers and producers about the importance of GI in boosting the production and maintenance of quality.